Investigation of using pumpkin seed oil methyl ester as a fuel in a boron coated diesel engine - Ozturk, Ugur; Hazar, Hanbey; Art, Yavuz Selim (Pergamon-Elsevier Science Ltd, 2019)
In this study, pumpkin seed oil was converted into biodiesel using alkali-catalyzed transesterification. Physicochemical properties were examined based on ASTM standards and compared with commercial diesel fuel (D-2). To improve the performance of engine, combustion chamber components like piston head, cylinder liner, intake and exhaust valves were thermally coated. Boronizing method was applied for the first time in the coating of conventional cast iron cylinder liner surface to reduce heat transfer. 150 mu m thick Fe2B layer was deposited on the surfaces. So, the conventional engine was converted into low heat rejection engine. In order to determine the insulation affect of Fe2B layer, 3-D finite element transient-state analyses were done to the both coated and standard cylinders. D-2 and PSME fuel blends were used as test fuels. Emission and performance of the coated engine (CE) have been investigated for both fuels. CE showed lower emission and higher performance. For D-2 and B-20 fuels; results showed that, CO decreased by 13-15%, HC decreased by 53-36%, smoke density decreased by 15-36%, respectively. But NOx emission increased by 11-37% for D-2/B-20 fuels, respectively. Besides, BTE for D-2/B-20 fuel increased by 10-10% while BSEC decreased by 3-9%, respectively. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Thermal barrier; Boronizing; Low heat rejection; Emission; Performance